Calcium-stimulated adenylyl cyclase subtype 1 (AC1) contributes to LTP in the insular cortex of adult mice. Issue 7 (July 2017) - Yamanaka, Manabu; Matsuura, Takanori; Pan, Haili; Zhuo, Min
Abstract: Long-term potentiation (LTP) of synaptic transmission in the central nervous system is a key form of cortical plasticity. The insular cortex (IC) is known to play important roles in pain perception, aversive memory and mood disorders. LTP has been recently reported in the IC, however, the signaling pathway for IC LTP remains unknown. Here, we investigated the synaptic mechanism of IC LTP. We found that IC LTP induced by the pairing protocol was N-methyl-D-aspartate receptors (NMDARs) dependent, and expressed postsynaptically, since paired-pulse ratio (PPR) was not affected. Postsynaptic calcium is important for the induction of post-LTP, since the postsynaptic application of BAPTA completely blocked the induction of LTP. Calcium-activated adenylyl cyclase subtype 1 (AC1) is required for potentiation. By contrast, AC8 is not required. Inhibition of Ca 2+ permeable α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (CP-AMPARs) or protein kinase M zeta (PKMζ) reduced the expression of LTP. Our results suggest that calcium-stimulated AC1, but not AC8, can be a trigger of the induction and maintenance of LTP in the IC.